Comparison of Icare Rebound Tonometer and Perkins Applanation Tonometer in Community Eye Screening - Ting, Siew Leng; Lim, Lik Thai; Ooi, Chor Yau; Md Mizanur, Rahman (Asia-Pacific Academy of Ophthalmology., 2019)
Purpose: To compare the measurement of intraocular pressure (IOP) of Icare rebound tonometer and Perkins applanation tonometer (PAT) during community eye screening and to assess the agreement between these 2 instruments. Design: A cross-sectional, non-interventional study. Methods: The IOP measurements by handheld Icare rebound tonometer (Finland) were first performed by a primary care physician. Then the IOP was measured using Perkins Mk3 applanation tonometer (Haag-Streit, UK) by an ophthalmologist who was masked to previous readings from the Icare rebound tonometer. The mean IOP measured by each tonometer was compared. Pearson correlation coefficient was used to explore the correlation between the IOP measurements of the 2 instruments. The level of agreement between them was assessed using the Bland and Altman method. Results: A total of 420 left eyes were examined. The mean age of subjects was 38.6 ± 18.2 years. Approximately 67% of subjects were female. The mean IOP was 16.3 ± 4.0 mm Hg using Icare and 13.4 ± 2.3 mm Hg using PAT. Pearson correlation coefficient showed a moderate positive correlation between the 2 methods (r = +0.524, P < 0.001). Linear regression analysis revealed a slope of 0.28 with R2 of 0.255. The mean difference between the 2 methods was 2.90 ± 3.5 mm Hg and the sample t-test revealed a statistically significant mean difference from 0 (P < 0.001). The 95% limits of agreement between the 2 methods were between −9.73 and 3.93 mm Hg. Conclusions: The handheld Icare rebound tonometer is a reasonably acceptable screening tool in community practices. However, Icare overestimated IOP with a mean of 2.90 mm Hg higher than the PAT. Thus, using Goldmann applanation tonometer as a confirmatory measurement tool of IOP is suggested.